الموقف الأوربي من الملف النووي الإیراني (ألمانیا أنموذجا) (Journal of the College of Education for Women, 2019)
The research tries to discuss the European attitude towards the Iranian nuclearactivities withen its ambitious nuclear program. It studies the European endeavor to settlethis problem peacefully or to solve it by exerting economic and diplomatic pressures on theIranian leadership so, it will give up its nuclear ambitions.Germany exerts single efforts and others withen the European Troika to follow upthe Iranian nuclear case attempting to prevent Iran from acquiring nuclear weapon whichgives Iran a distinguished regional status. Thus , this situation will lead the current regionalequivalence become unbalanced as well as it is conducive to dangerous consequences , toendanger the security of Israel is the most important one.Germany endeavors to increase its economic and commercial interests in Iran toensure its presence singly or withen the framework of European Troika in the region in away that will enhance its role and that of the European Union.In fact, Germany aims to play an active and influential role in addressing internationalevents.In spite of its efforts that aim to appeasement in dealing with the Iranian nucleardossier through dialogue or negotiation .Its attitude will be unaccepted if the doubts concerning Iranian intentions and havingcapability to produce nuclear weapon in a way that will endanger Israel security will beensured. In this case Germany will support the western attitude that refuses the Iranianambitions.